Morphological and molecular characterization of stigonema jureiensis sp. Nov. (nostocales, cyanobacteria) from the atlantic rainforest, são paulo, brazil - Hentschke, Guilherme S.; Rigonato, Janaína [UNESP]; Genuário, Diego B.; Laughinghouse, Haywood D.; Sant‘anna, Célia L. (Palacky University Olomouc, 2019)
Tropical regions are considered hotspots of biodiversity, and the genus Stigonema has been underexplored in all world, mainly due to the difficulties of culturing. In this study, we sequenced the 16S rRNA gene of a natural Stigonema population from the tropical Atlantic Rainforest (São Paulo, Brazil) and describe S. jureiensis sp. nov. based on phylogenetic and morphological data. For the molecular analysis, the genomic DNA was isolated from aliquots of the population, which were previously manually cleaned under a microscope, using a point–tapered Pasteur pipette to remove other organisms and debris. For morphological analysis, 30 individuals were analyzed and photographed using microscope. Both maximum likelihood and Bayesian phylogenies support S. jureiensis as a new species, and morphological analysis revealed the presence of a special type of mosaic ornate sheaths.
Keywords: Biodiversity; Microorganism; Polyphasic approach; Taxonomy; Terrestrial habitats; Tropical environments